SARCOPENIA PREVALENCE AND ASSOCIATED FACTORS IN ELDERLY (Movimenta (ISSN 1984-4298), 2022)
Aging is a degenerative, progressive and complex process that involves physiological, psychological and social factors. Sarcopenia is defined as a progressive and generalized muscle syndrome that negatively affects muscle strength and causes a reduction in muscle mass. The aim of the study was to identify the prevalence and factors associated with sarcopenia in Brazilian community-dwelling elderly people through an integrative literature review. This is, therefore, an integrative literature review, carried out by electronic search in the following databases: PUBMED, MEDLINE and LILACS via the Virtual Health Library (BVS), PEDro (Physiotherapy Evidence Database) and SCIELO in the period of March 2021 to February 2022. The descriptors used were chosen by consulting the Health Sciences Descriptors (DeCS), using the following combinations of descriptors in English, Spanish and Portuguese: “Aged” OR “Aged,80 and over” OR “ Elderly” AND “Prevalence” AND “Sarcopenia” AND “Brazil; “Anciano” AND “Prevalence” AND “Sarcopenia” AND “Brazil”; “Elderly” AND “Prevalence” AND “Sarcopenia” AND “Brazil”. A total of 1161 articles were analyzed, and in the end only 6 articles were included, while 37 were excluded. The prevalence of sarcopenia ranged from 3.1% to 55.8% and the main factors associated with its occurrence were advanced age, low education, smoker, low income, presence of comorbidities, malnutrition and/or risk of malnutrition and5 physical inactivity . The prevalence of sarcopenia in Brazilian community-dwelling elderly people ranges from 3.1 to 55.8% and advanced age, low education, low income, malnutrition, associated comorbidities and physical inactivity are factors most associated with sarcopenia.
Keywords: Aged; Aged, 80 and over; Elderly; Prevalence; Sarcopenia